Mitochondria-mediated apoptosis in mammals. Issue 10 (31st July 2014) - Xiong, Shunbin; Mu, Tianyang; Wang, Guowen; Jiang, Xuejun
Abstract: The mitochondria-mediated caspase activation pathway is a major apoptotic pathway characterized by mitochondrial outer membrane permeabilization (MOMP) and subsequent release of cytochrome c into the cytoplasm to activate caspases. MOMP is regulated by the Bcl-2 family of proteins. This pathway plays important roles not only in normal development, maintenance of tissue homeostasis and the regulation of immune system, but also in human diseases such as immune disorders, neurodegeneration and cancer. In the past decades the molecular basis of this pathway and the regulatory mechanism have been comprehensively studied, yet a great deal of new evidence indicates that cytochrome c release from mitochondria does not always lead to irreversible cell death, and that caspase activation can also have non-death functions. Thus, many unsolved questions and new challenges are still remaining. Furthermore, the dysfunction of this pathway involved in cancer development is obvious, and targeting the pathway as a therapeutic strategy has been extensively explored, but the efficacy of the targeted therapies is still under development. In this review we will discuss the mitochondria-mediated apoptosis pathway and its physiological roles and therapeutic implications.